Omega-3 Fatty Acids Reduce Inflammation in Rat Apical Periodontitis - Azuma, Mariane Maffei [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Ervolino, Edilson [UNESP]; Cardoso, Carolina de Barros Moraes [UNESP]; Pipa, Camila Barbosa [UNESP]; Kawai, Toshihisa; Conti, Leticia Citelli [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier, 2018)
Introduction: The effects of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) on pro- and anti-inflammatory mediators were evaluated in a rat model of pulp exposure–induced apical periodontitis (AP). Methods: Twenty-eight male Wistar rats were divided into 4 groups: control, untreated rats (group C); control rats treated with ω-3 PUFAs (group C-O); rats with pulp exposure–induced AP (group AP); and rats with pulp exposure–induced AP treated with ω-3 PUFAs (group AP-O). Omega-3 PUFAs were administered orally once a day for 15 days before pulp exposure; this treatment was continued for 30 days after pulp exposure. The rats were sacrificed 30 days after pulp exposure, and their dissected jaws were subjected to immunohistochemical analysis to detect immunoreactivity for tumor necrosis factor alpha (TNF-α), interleukin (IL)-6, IL-1β, IL-17, and IL-10 on the periapical bone surface. The results were statistically evaluated using analysis of variance and the Tukey post-test. The significance level was set at 5%. Results: Immunoreactivity for the proinflammatory cytokines TNF-α, IL-6, IL-1β, and IL-17 was higher in the AP group than in the AP-O, C, and C-O groups (P <.05). Immunoreactivity for the anti-inflammatory cytokine IL-10 was lower in the AP group than in the AP-O group (P <.05). Conclusions: Supplementation with ω-3 PUFAs can modulate the inflammatory response in rat AP, decreasing levels of TNF-α, IL-6, IL-1β, and IL-17 but increasing levels of IL-10.
Keywords: Apical periodontitis; cytokine, endodontic infection; omega-3 fatty acid